Hydrogen peroxide formation in carbon clothes for enhancement of an electro-oxidation tertiary treatment for tequila vinasse wastewater - Covarrubias-Del-Toro, Rafael; Huerta-Rocha, Marisol; Lezama, Luis; García, Edith Xio Mara; Estrada-Vargas, Arturo (Frontiers in Environmental Science, 2023)
Carbon-based electrodes have been extensively used as cathodes for the electro-generation of H₂O₂, which is used in the production of the hydroxyl radical •OH to mineralize organic compounds in several types of wastewater. Carbon cloth has been also used in combination with activated carbon for the combined adsorption and oxidation of persistent organic compounds present in tequila vinasse wastewater. Whereas most of the works regarding the H₂O₂ electro-generation involve relatively complex processes to enhance the catalytic activity or the electrochemically active area of these electrodes, calcination by itself represents a simple and low-cost option to enhance these cathodic and anodic functions, especially in the fabrication of large area electrodes that could be needed to treat the large amount of tequila vinasse wastewater that is produced daily. In this work, the effect of calcination at 300 and 600 °C of carbon clothes in the oxidation current and H₂O₂ production at different potentials in H₂SO₄ was studied. Oxidation current increased 700 % upon calcination at 600 °C, compared to no calcination. H₂O₂ was produced only in a narrow range of polarizations, whereas calcination at 600 °C increased the generation rate from 7.1 ± 0.3 to 17.8 ± 0.4 mg l⁻¹ h⁻¹.